The effects of water quality on the growth of lumpfish (Cyclopterus lumpus) - Amber Christina Monroe 1992- (2021)
Lumpfish (Cyclopterus lumpus) are of economic value as a biological lice control of Atlantic salmon (Salmo salar) in sea cages, reducing or eliminating the need for chemical or mechanical treatments for sea lice (Lepeophtheirus salmonis, Caligus elongatus). Lumpfish aquaculture production is still in early stages and there is a paucity of information available on the physiological requirements of the species, particularly the effects of water quality on fish welfare and growth. The objective of this study, which consisted of two experiments, was to examine the effects of different water quality parameters on the growth and survival of lumpfish. The water quality parameters studied were CO2, total ammonia nitrogen (TAN – nitrogen bound as either NH3 or NH4+) and pH. The results indicate that pH in the range tested (7.2-7.8) does not directly affect the growth of lumpfish. However, reduced pH can increase the CO2 concentration which in turn may affect the growth of lumpfish, even at 8 mg·l-1. Growth is further reduced at higher CO2 concentration (15 mg·l¬1). TAN is the combined amount of NH3 and NH4+ and the proportion of each ion is determined by pH. NH3 affects the growth and survival of fish, while NH4+ is thought to have no or more benign effects. The results of the present study show that NH3 at relatively low concentrations (0.08 mg·l-1) can affect the growth of lumpfish. Interestingly, increased NH4+ concentration (33 mg·l-1) can also reduce the growth of lumpfish. In both experiments, the control fish grew the best but growth was reduced when reared in low concentrations of CO2 and NH3. Taken together, the results of the experiments suggests that lumpfish are sensitive to perturbations in water quality. Moreover, the results provide a basis for improving welfare indicators for lumpfish aquaculture. Hrognkelsi (Cyclopterus lumpus) geta haldið aftur af lúsasmiti á laxi (Salmo salar) í eldiskvíum og þannig dregið úr þörf fyrir meðhöndlun gegn laxa- og fiskilús (Lepeophtheirus salmonis, Caligus elongatus) ...